KONSEP DOXA DALAM BUDAYA BALI DAN MAKASSAR: KOMPARASI TEKS GEGURITAN JAYAPRANA DAN SINRILIK I DATUK MUSENG - Rahmatia Ayu Widyaningrum (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2024)
Abstrak Tulisan ini mengungkapkan konsep doxa yang terdapat di dalam teks Geguritan Jayaprana dan Sinrilik I Datu Museng. Keduanya adalah teks yang berkisah tentang lingkungan istana yang memiliki legitimasi membangun konstruksi budaya. Geguritan yang berbentuk puisi dibacakan dengan cara ditembangkan, begitu pula dengan Sinrilik yang disampaikan melalui nyanyian atau deklamasi dengan iringan musik tradisional. Keduanya berasal dari dua budaya berbeda, yaitu Bali dan Makassar. Namun, kedua karya sastra ini menggambarkan konsep doxa yang dianggap sebagai sebuah kebenaran tanpa perlu diperdebatkan. Terdapat perbedaan wacana dalam konsep doxa keduanya. Dalam Geguritan Jayaprana, konsep doxa yang dipakai adalah wacana orthodoxy atas tunduknya Jayaprana terhadap titah raja dan pati wrata (bunuh diri) yang dilakukan oleh Ni Layonsari sebagai bentuk kesetiaan istri kepada suaminya. Berbeda halnya dengan kisah dalam Sinrilik I Datu Museng, konsep doxa yang terlihat adalah wacana heterodoxy dengan berusaha melawan nilai-nilai yang berlaku yang diberikan oleh kelompok dominan (penjajah). Budaya siri’ untuk membela harga diri adalah hal yang wajib dilakukan dalam tradisi Bugis dan Makassar, seperti halnya semangat puputan yang terjadi di Bali. Kata Kunci: Doxa, Geguritan, Sinrilik, Bali, Makassar. Abstract This article elaborates on the concept of doxa as portrayed in the texts Geguritan Jayaprana and Sinrilik I Datu Museng, originating from revered royal settings and carrying significant cultural weight. Geguritan is presented in poetic form, and recited through singing, while Sinrilik is conveyed through singing or declamation with traditional musical accompaniment. Despite their distinct cultural origins in Bali and Makassar, both texts exemplify doxa as an accepted truth that transcends debate. It is important to note the disparities in the discourse surrounding the concept of doxa within both texts. In Geguritan Jayaprana, the concept of doxa highlights the discourse of orthodoxy, emphasizing Jayaprana's adherence to the king's command and Ni Layonsari's pati wrata (suicide) as an expression of spousal loyalty. Conversely, in Sinrilik I Datu Museng, the concept of doxa is rooted in the discourse of heterodoxy, depicting resistance against the prevailing values of the dominant colonizers. The cultural practice of siri', aimed at defending one's honor, is an obligatory facet of Bugis and Makassar traditions, akin to the puputan spirit in Bali. Keywords: Doksa, Geguritan, Sinrilik, Bali, Makassar, This article elaborates on the concept of doxa as portrayed in the texts Geguritan Jayaprana and Sinrilik I Datu Museng, originating from revered royal settings and carrying significant cultural weight. Geguritan is presented in poetic form, and recited through singing, while Sinrilik is conveyed through singing or declamation with traditional musical accompaniment. Despite their distinct cultural origins in Bali and Makassar, both texts exemplify doxa as an accepted truth that transcends debate. The concept of doxa is investigated within the framework of genetic structuralism theory, also known as Pierre Felix Bourdieu's constructivist structuralism. It is important to note the disparities in the discourse surrounding the concept of doxa within both texts. In Geguritan Jayaprana, the concept of doxa highlights the discourse of orthodoxy, emphasizing Jayaprana's adherence to the king's command and Ni Layonsari's pati wrata (suicide) as an expression of spousal loyalty. Conversely, in Sinrilik I Datu Museng, the concept of doxa is rooted in the discourse of heterodoxy, depicting resistance against the prevailing values of the dominant colonizers. The cultural practice of siri', aimed at defending one's honor, is an obligatory facet of Bugis and Makassar traditions, akin to the puputan spirit in Bali. Keywords: Doksa, Geguritan, Sinrilik, Bali, Makassar,